Experimental model in vitro of white piedra and evaluation of the susceptibility profile of Trichosporon against thiophene-tiosemicarbazone derivatives (L10) (Research, Society and Development, 2021)
The aim of the present study was to evaluate the in vitro pathogenicity potential and the susceptibility profile of Trichosporon spp. to thiophene-thiosemicarbazone derivatives(L10). At first, a taxonomic review of 3 Trichosporon spp. of clinical importance stored at the URM Micoteca of the Federal University of Pernambuco (UFPE). Posteriorly, the capacity of these species to grow in vitro in healthy hair (free from chemical treatments) at 25 °C and 37 °C for a period of 10 days was evaluated. After this period, direct examination of the hair was performed, using 10% KOH, and cultured in Sabouraud Agar medium with chloramphenicol of the samples that grew in the hair, as well as analyzes of the macro and micromorphology of these fungal species. Finaly, the in vitro susceptibility profile of these fungal species to thiophene-thiosemicarbazone (L10) derivatives was performed according to the Clinical and Laboratory Standards Institute (CLSI) to determine minimal inhibitory concentrations (MICs) and minimal fungicidal concentrations (MFCs). Through the in vitro experimental model, it was possible to observe the following species: Trichosporon asahii, T. ovoides and T. cutaneum are etiological agents of white piedra and present pathogenic potential even in an in vitro experimental modelwithout the need for synergism with other types of microorganisms. Through the analysis of the in vitro susceptibility profile, it was possible to observe that the new thiophene derivatives tested are not effective to inhibit the growth of the evaluated Trichosporon species, thus being inadequate for the treatment of clinical manifestations observed in white piedra. In conclusion, this study showed that it is possible to cultivate Trichosporon in an in vitro model and that searches for other effective therapeutic approaches are necessary to combat infections caused by fungi of the genus Trichosporon.